Healing Behind Bars: The Role of Guilt, Shame, and Forgiveness in Rebuilding Prisoners Future Orientation - Garinda Aldo Rasyidan (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The high rate of recidivism in correctional institutions in Indonesia, which indicates that the rehabilitation and guidance process for prisoners has not been entirely successful, particularly in addressing psychological aspects. This condition indicates the need for a guidance approach that pays attention to moral emotional factors such as guilt, shame, and forgiveness, which play an important role in shaping the future orientation of prisoners. The purpose of this study was to examine the influence of guilt, shame, and forgiveness on the future orientation of repeat offenders in the Kediri Class IIA Correctional Institution. This study used a quantitative approach with a correlational design. The sample consisted of 160 repeat offenders selected by purposive sampling from a total population of 235 people. The research instruments included the Offence-Related Feelings of Shame and Guilt Scale (ORSGS), Heartland Forgiveness Scale (HFS), and Future Orientation Scale (FOS), with data analysis using multiple linear regression. The results of this study reveal that guilt and shame (β = 0.594; p < 0.001) and forgiveness (β = 0.352; p < 0.001) have a significant effect on future orientation, both partially and simultaneously, with a total contribution of 88.1%. The implications of this study indicate the importance of strengthening moral emotions and the ability to forgive in prisoner rehabilitation programs to support psychological recovery, strengthen future orientation, and reduce recidivism rates in Indonesia.